Sabino Arana Goiri eta hiperbizkaiera (Hiperbizkaieraren historiaz III) - Laka, Itziar (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1987)
In this article we attempt to analyse the part played by Sabino Arana -a character who cannot be neglected when dealing with this period- in the development of Hiperbiscayan. We haye tried first of all to define the areas of research nurtured in Basque studies by Arana really restricted himself principally to the field of words: phonetics, etymology and neologisms, he very rarely dealt with other fields, like morphology or syntax. In his work, therefore, there are no more than the briefest analyses to be found on the verb or its morphology, whilst the opposite is to be seen in Azkue (cf. my essay on the latter published in ASJU XX-3 (1986)). Despite this, we have collected together his opinions on the subject, even those scattered in occasional notes; and this being little on which to base a definition of his position as regards the nascent Hiperbiscayan, we have also examined his texts in Basque. As a result of our study, we can hold that Arana did not use the model proposed by Azkue until 1897, and that he left no reference to it in his writings even after starting to use it. We may speculate that Arana did not realise the purpose of Azkue's proposal in Euskal-Izkindea ("Basque Grammar", 1891), which was that in Azkue's opinion the dialect of Biscay had to be cleaned up also in so far as the verb was concerned. Indeed, some passages of Arana's writings seem to indicate that Arana believed that the model proposed by Azkue was one already spoken in some parts of Biscay. We round off the article by examining the incomplete study of the verb left by Arana at his death.